Pengaruh Kompensasi Manajemen, Kepemilikan Institusional dan Intensitas Persediaan terhadap Manajemen Pajak - Valencia Diaz Puspita Maharani; Rakhmawati Oktavianna (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
This research aims to test and obtain empirical evidence regarding management compensation, institutional ownership, and inventory intensity on tax management in non-cyclical consumer sector companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The type of research used is quantitative research with secondary data in the form of annual reports for the 2018-2022 period obtained from the official website of the Indonesian Stock Exchange and the official websites of each company. The total population is 114 companies in the Consumer Non-Cyclicals sector for the 2018-2022 period, the number of samples in this study is 105 observation data from 21 companies in the Consumer Non-Cyclicals sector for the 2018-2022 period which was obtained using the purposive sampling method. The data analysis technique used is descriptive statistics and panel data regression analysis using eviews-10. The research results based on simultaneous tests with the f test state that management compensation, institutional ownership, and inventory intensity have a simultaneous and significant effect on tax management. based on a partial test with a t test, it states that management compensation has no effect on tax management, institutional ownership has a significant effect on tax management, and inventory intensity has no effect on tax management.